COMPLIANCE TO SURVIVING SEPSIS CAMPAIGN HOUR–1 BUNDLE–A CROSS SECTIONAL STUDY AMONG PHYSICIANS INVOLVED IN CRITICAL CARE IN PAKISTAN - Feroze, Rehana; Tariq, Muhammad; Toor, Abdul Wasay (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine physician’s compliance to surviving sepsis campaign updated Hour-one bundle in critically ill patients in Pakistan. Study Design: Cross-sectional study. Place and Duration of Study: Department of Anaesthesiology, Combined Military Hospital Lahore Medical College, from Jun to Aug 2019. Methodology: This study was carried out among physicians managing critical patients in intensive care units. Participants were asked to fill out a 16-questions survey (work experience, qualification and individual components of surviving sepsis campaign hour-1 bundle. Data was collected using online access to survey and by sending hard copies. Results: Questionnaire was sent to 230 physicians while only 63 responses were received (response rate 27%). Only 45 (71%) respondents were aware of the updated Hour-1 bundle. There was no institutional protocol for compliance to sepsis bundles in thirty three (55%) responses. 52% respondents used Systemic inflammatory response syndrome (SIRS) criteria to diagnose sepsis while quick Sequential Organ Failure Assessment (qSOFA) was used by 36% respondents. Overall compliance to hour-1 bundle components was only 60%. Lactate levels was not measured by 35 (55%) respondents while 24 (38%) did not obtain blood cultures before administering antibiotics. Crystalloid and nor epinephrine was used by all respondents. Overall compliance with all the components of sepsis bundle had strong correlation with post-graduate qualification (p-value 0.001-0.049). Conclusion: Poor compliance to updated sepsis guidelines was one of the major reasons of high sepsis related mortality in Pakistan.